Ctenopharyngodon Idella STAT3 alleviates autophagy by up-regulating BCL-2 expression. Issue 91 (August 2019) - Chen, Xingxing; Han, Kun; Lin, Gang; Liu, Changxin; Wang, Shanghong; Shi, Xiao; Hu, Zhizhen; Wu, Chuxin; Xu, Xiaowen; Hu, Chengyu
Abstract: In mammals, STAT3 (Signal transducer and activator of transcription 3) plays an absolutely vital role in response to cytokines and growth factors. In mammals, IL-6/JAK/STAT3 pathway is closely linked to immune response and promotes cell proliferation, survival and metastasis. Some recent studies have already demonstrated that STAT3 regulates autophagy. As a downstream target gene of STAT3, Bcl-2 (B-cell lymphoma 2) not only participates in regulating apoptosis, but also responds to autophagy. STAT3 regulates autophagy through Bcl-2. In general, the generation of autophagy is always accompanied by the change of apoptosis, and the occurrence of apoptosis is often accompanied by the decreased of cell viability. In grass carp ( Ctenopharyngodon idella ), LPS-induced autophagy is involved in the release of pro-inflammatory cytokines. However, only the relationship between autophagy and cytokines was illustrated, in which the signaling pathways were not discussed. In the present study, we found that the autophagy inducer, Tunicamycin (Tm), can induce C.Idella Kidney cells (CIK) autophagy. When the cells were incubated with the recombinant human IL-6 (rIL-6) for a short period of times, the mRNA expression level of C.Idella IL-6R and STAT3 were increased. At the same time, the number of GFP-LC3 puncta and the ratio of LC3-II/LC3-I were both decreased obviously in cells. It indicated that the rIL-6 can significantly alleviate autophagy induced by Tm. We speculated that CiSTAT3 may play a key role in the process. To confirm this hypothesis, we performed a rIL-6 activating CiSTAT3 assay. The result demonstrated that rIL-6 can induce CiSTAT3 to form homologous dimmer. The activated CiSTAT3 regulated the transcription activity of CiBcl-2, finally led to a decrease of autophagy. In addition, when cells were in the state of autophagy, apoptosis was increased and cell viability was decreased. When CiSTAT3 was activated, cell apoptosis weakened and cell viability was increased. The results suggest that CiSTAT3 plays an important role in maintaining the normal physiological process of cells. Highlights: Grass Carp STAT3 can respond autophagy. Grass Carp STAT3 can form the homodimer after incubation of rIL-6. The activation of CiSTAT3 can decreased apoptosis and enhance cell viability. Grass Carp STAT3 up-regulate the transcriptional levels of Grass Carp Bcl-2.